2015
DOI: 10.1177/0042098015583229
|View full text |Cite
|
Sign up to set email alerts
|

Financialisation, the valuation of investment property and the urban built environment in the UK

Abstract: The financialisation literature has been criticised for its limited empirical base and its failure adequately to link the everyday world with that of high finance. The paper addresses these shortcomings by examining the calculative practice of property valuation. The way that valuations are performed affects their results and, therefore, the operation of the property market. The paper traces the evolving influence of finance capital on the valuation of commercial property in the UK by constructing a historiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 55 publications
(85 reference statements)
0
62
0
4
Order By: Relevance
“…The overall strategy of financialization was accomplished by means of comprehensive income-generating securities or collateralized mortgage obligations (CMOs) such as mortgaged-backed securities (MBS) and structured investment vehicles (SIVs) based on the aggregation of large numbers of individual mortgages into massive investment pools (Gothan 2012;O'Neil, 2018). The new-found ability to securitize real-estate debt in this way offered enormous windfall profits to financial institutions, including global giants like Bear Sterns, Lehman Brothers, Merrill Lynch, J.P. Morgan, and Wachovia (Crosby and Henneberry, 2016). Institutions like these, in partnership with commercial banks, issued commercial paper that in effect shifted money from the international financial system down to individual real estate purchasers and then transferred the concomitant interest payments back up to holders (many of them insurance companies and large pension funds) of the paper.…”
Section: Real-estate Markets and Financementioning
confidence: 99%
“…The overall strategy of financialization was accomplished by means of comprehensive income-generating securities or collateralized mortgage obligations (CMOs) such as mortgaged-backed securities (MBS) and structured investment vehicles (SIVs) based on the aggregation of large numbers of individual mortgages into massive investment pools (Gothan 2012;O'Neil, 2018). The new-found ability to securitize real-estate debt in this way offered enormous windfall profits to financial institutions, including global giants like Bear Sterns, Lehman Brothers, Merrill Lynch, J.P. Morgan, and Wachovia (Crosby and Henneberry, 2016). Institutions like these, in partnership with commercial banks, issued commercial paper that in effect shifted money from the international financial system down to individual real estate purchasers and then transferred the concomitant interest payments back up to holders (many of them insurance companies and large pension funds) of the paper.…”
Section: Real-estate Markets and Financementioning
confidence: 99%
“…Having followed up the evolutionary effect that the financial capital has upon on the commercial property valuation in the UK through preparing a historiography of the investment cost measurement beginning from 1960, thus supporting views of Crosby and Henneberry (2016), it has been found that in consideration of fair value measurement weaknesses the traditional valuation method still prevails for measurement of the market value (Crosby & Henneberry, 2016).…”
Section: Cushman and Wakefield's Quarterly Europeanmentioning
confidence: 80%
“…The growth of calculative practices, which are based on rationalist paradigms of mainstream financial economic methods, are being gradually incorporated into a broad range of public policies. As a result, traditional approaches to the valuation of programmes and assets are being increasingly challenged and affected by financial economics (Christophers, 2017;Crosby and Henneberry, 2016). Financialisation is having an ever-stronger impact on the determination of 'what should' and 'should not' be considered during the processes of valuation (Halbert and Attuyer, 2016).…”
Section: The Financialisation Of Local Government and The Rise Of Viamentioning
confidence: 99%